Improving Use of Targeted Temperature Management After Out-of-Hospital Cardiac Arrest: A Stepped Wedge Cluster Randomized Controlled Trial*. Issue 5 (May 2015) - Morrison, Laurie J.; Brooks, Steven C.; Dainty, Katie N.; Dorian, Paul; Needham, Dale M.; Ferguson, Niall D.; Rubenfeld, Gordon D.; Slutsky, Arthur S.; Wax, Randy S.; Zwarenstein, Merrick; Thorpe, Kevin; Zhan, Cathy; et al.
Abstract : Rationale: International guidelines recommend use of targeted temperature management following resuscitation from out-of-hospital cardiac arrest. This treatment, however, is often neglected or delayed. Objective: To determine whether multifaceted quality improvement interventions would increase the proportion of eligible patients receiving successful targeted temperature management. Setting: A network of 6 regional emergency medical services systems and 32 academic and community hospitals serving a population of 8.8 million people providing post arrest care to out-of-hospital cardiac arrest. Interventions: Comparing interventions improve the implementation of targeted temperature management post out-of-hospital cardiac arrest through passive (education, generic protocol, order set, local champions) versus additional active quality improvement interventions (nurse specialist providing site-specific interventions, monthly audit-feedback, network educational events, internet blog) versus no intervention (baseline standard of care). Measurements and Main Results: The primary process outcome was proportion of eligible patients receiving successful targeted temperature management, defined as a target temperature of 32-34ºC within 6 hours of emergency department arrival. Secondary clinical outcomes included survival and neurological outcome at hospital discharge. Four thousand three hundred seventeen out-of-hospital cardiac arrests were transported to hospital; 1, 737 (40%) achieved spontaneous circulation, and 934 (22%) were eligible for targeted temperature management. After accounting for secular trends, patients admitted during the passive quality improvement phase were more likely to achieve successful targeted temperature management compared with those admitted during the baseline period (25.7% passive vs 9.0% baseline; odds ratio, 2.76; 95% CI, 1.76–4.32; p < 0.001). Active quality improvement interventions conferred no additional improvements in rates of successful targeted temperature management (26.9% active vs 25.7% passive; odds ratio, 0.96; 95% CI, 0.63–1.45; p = 0.84). Despite a significant increase in rates of successful targeted temperature management, survival to hospital discharge was unchanged. Conclusion: Simple quality improvement interventions significantly increased the rates of achieving successful targeted temperature management following out-of-hospital cardiac arrest in a large network of hospitals but did not improve clinical outcomes. Abstract : Supplemental Digital Content is available in the text.